2010
DOI: 10.1095/biolreprod.109.080028
|View full text |Cite
|
Sign up to set email alerts
|

Tubulointerstitial Nephritis Antigen-Like 1 Is Expressed in the Uterus and Binds with Integrins in Decidualized Endometrium During Postimplantation in Mice1

Abstract: Extracellular matrix substrates contribute to both uterine and blastocyst functions during the peri-implantation period. Tubulointerstitial nephritis antigen-like 1 (TINAGL1, also known as adrenocortical zonation factor 1 [AZ-1] or lipocalin 7) is a novel matricellular protein that promotes cell adhesion and spreading. However, the physiological roles of TINAGL1 are still not clearly understood. We examined the expression and localization of TINAGL1 in peri-implantation mouse uteri. During the preimplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Probes had specific activities of about 2 × 10 9 dpm/μg. Uterine tissues were snap-frozen using freezing solution (FREEZER, HOZAN, Osaka, Japan) as described previously [21,22]. Frozen sections (10 μm) were prepared with a cryostat, mounted onto poly-L-lysine-coated slides and fixed in cold 4% paraformaldehyde in phosphate-buffered saline.…”
mentioning
confidence: 99%
“…Probes had specific activities of about 2 × 10 9 dpm/μg. Uterine tissues were snap-frozen using freezing solution (FREEZER, HOZAN, Osaka, Japan) as described previously [21,22]. Frozen sections (10 μm) were prepared with a cryostat, mounted onto poly-L-lysine-coated slides and fixed in cold 4% paraformaldehyde in phosphate-buffered saline.…”
mentioning
confidence: 99%
“…Lipocalin-7 is a potent integrin ligand that has emerged as an important promoter of cell adhesion and spreading through interactions with ECM proteins and integrins (Tajiri et al, 2010). Brown et al (2010) demonstrated that lipocalin-7 is a positive regulator of angiogenesis that increases endothelial cell invasion, angiogenic cell …”
Section: Extracellular Integrin Ligandsmentioning
confidence: 99%
“…In particular, TINAGL1 is a novel component of the Reichert's membrane that interacts with laminin 1 [49]. In contrast, it associates with integrins a5 and b1 in the decidualized uterine endometrium [51].…”
Section: Extracellular Proteins and Tinagl1 In The Basement Membrane mentioning
confidence: 99%